The Contribution of Information Technology to Human Resource Development in Sports Institutions (A Field Study within the Directorate of Youth and Sports - M’Sila) - Hadjab, abdelkarim; bait, Aissa (sports creativity, 2024)
This study aims to determine the extent to which information technology, with its multifaceted components, contributes to human resource development in Algerian sports institutions. The success of these institutions in achieving their goals stems from the human resources department's interest in developing human capital as the crucial factor in carrying out various tasks. This can only be achieved through the development and training of human resources using information technology. In this study, the descriptive approach was used on a sample of 20 employees in M’Sila’s Directorate of Youth and Sports. The questionnaire was used as a tool for collecting data. The most important results of the study indicated that information technology contributes significantly to the development of human resources in sports institutions. Based on the projected outcomes, a crucial recommendation is posited: the eradication of digital illiteracy among personnel through the implementation of continuous training programs focused on information technology proficiency.